A Systems Engineering Approach for the Design of an Omnidirectional Autonomous Guided Vehicle (AGV) Testing Prototype. (21st March 2022) - Tejada, Juan C.; Toro-Ossaba, Alejandro; Muñoz Montoya, Santiago; Rúa, Santiago
Abstract : This paper addresses the mechanical and electrical design of an autonomous guided vehicle (AGV) test prototype based on a systems engineering approach. First, the different phases of the systems engineering approach are described. The conceptual design begins with the house of quality, which weighs the relevance of each user requirement and ends with a functional representation of the vehicle. Then, the mechanical and electrical design are presented considering different subsystems such as the chassis, cargo platform, suspension system, power, and control components. Finally, different tests were carried out on the prototype, validating its movement and load capacities. The systems engineering approach as a methodology for the construction of complex systems has proven to be an excellent tool for the development of autonomous guided vehicles.